Accounting can support a "sustainable" corruption network: a case analysis. Issue 1 (19th June 2020) - Pilonato, Silvia
Abstract : Purpose: The paper aims to explore the links between corruption and accounting in the public procurement setting. In particular, it investigates how accounting can fight or facilitate corruption Design/methodology/approach: The study takes a qualitative approach, analyzing one of the worst recent Italian cases of corruption, the "MOSE" trial. Documents produced during the trial are analyzed. Findings: The findings contribute to our understanding of how the (mis)use of accounting can help to build a "sustainable" corruption network, and be used to create, maintain and share corruptive cash flows. Participating actors can use accounting tools to coordinate their actions and organize their misconduct. Accounting may also reveal the existence of such networks, however, by enabling the fiscal police to discover tax fraud, and by reconstructing how a corruption network functions from records kept to manage internal cash flows and the provision of other benefits. Practical implications: Because corruption is a worldwide phenomenon, a better understanding of how it functions may lead (among other things) to the identification of more effective prevention measures. Particular attention should be paid to events that favor corruption, such as extraordinary occurrences, huge amounts of public resources and new institutional structure without appropriate control and balance tools. Originality/value: Given the specific features of episodes of corruption, qualitative studies on this topic are scarce. Little is known about corruption processes, and even less about the part that accounting can play in them. The MOSE case offers some intriguing insight, showing how accounting can be used to build a "sustainable" corruption network by collecting slush funds and facilitating benefit-sharing among individuals.